‘Who’s a Proficient Second language learner?’ Evidence from Compound Formation - Tzakosta, Marina; Koufou, Konstantina-Eirini (Education Sciences, 2020)
This paper evaluates the ability of Albanian second language learners of Greek to form compound words. 15 Albanian learners of Greek participated in an off-line experimental task and were asked to form existing compounds as well as non-existing compound forms which are morphologically possible/ acceptable but semantically non-acceptable or vague. Emphasis is placed on a) compounds’ internal structure, b) headedness, c) the relation holding between compound elements as well as the status of linking elements, and d) the relevance of the above to various categories of compound words in Greek. The findings reveal that, compared to other groups of Albanian learners of Greek who have not attended the Greek educational system, the participants in the current study display very high scores in the tested linguistic tasks, similar to those of native speakers. We argue that high language proficiency level is attributed to language teaching strategies and methods applied at school.